2015
DOI: 10.2527/jas.2015-9377
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to infectious diseases is a heritable trait in rabbits1

Abstract: Selection for disease resistance is a powerful way to improve the health status of herds and to reduce the use of antibiotics. The objectives of this study were to estimate 1) the genetic parameters for simple visually assessed disease syndromes and for a composite trait of resistance to infectious disease including all syndromes and 2) their genetic correlations with production traits in a rabbit population. Disease symptoms were recorded in the selection herds of 2 commercial paternal rabbit lines during wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 18 publications
4
20
1
2
Order By: Relevance
“…Hazards for rhinitis can be divided into 2 main groups: predisposing hazards were linked with the line or breed of rabbits, and age, whereas enabling hazards were mainly related with the incorrect combination of the ambient temperature, humidity and air speed (Calvet et al, 2011;da Borso et al, 2016). A genetic component to resistance to Pasteurella has been identified (Gunia et al, 2015(Gunia et al, , 2018Shrestha et al, 2019); however, currently commercial lines are not characterised for this trait. Table 33 summarises the information on the main hazards for this welfare consequence and their degree of scientific support.…”
Section: Reproducing Doesmentioning
confidence: 99%
“…Hazards for rhinitis can be divided into 2 main groups: predisposing hazards were linked with the line or breed of rabbits, and age, whereas enabling hazards were mainly related with the incorrect combination of the ambient temperature, humidity and air speed (Calvet et al, 2011;da Borso et al, 2016). A genetic component to resistance to Pasteurella has been identified (Gunia et al, 2015(Gunia et al, , 2018Shrestha et al, 2019); however, currently commercial lines are not characterised for this trait. Table 33 summarises the information on the main hazards for this welfare consequence and their degree of scientific support.…”
Section: Reproducing Doesmentioning
confidence: 99%
“…To implement such selection, there is still a need for phenotypes that can be easily measured, at a reasonable cost (Merks et al, 2012 ). In rabbits, previous studies have shown that simple health records, measured once on growing animals of the selection nucleus, can be used to improve disease resistance (Eady et al, 2007 ; Garreau et al, 2012 ; Gunia et al, 2015 ). However, it is not known if such selection will be beneficial for maintaining the health and productivity of animals reared in commercial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Une alternative consiste à sélectionner pour la résistance aux troubles infectieux non spécifiques (Gunia et al, 2015). Mais une approche encore plus globale consiste à améliorer l'immunocompétence générale des animaux, en sélectionnant sur un ensemble de caractères héritables représentatifs des différentes facettes de la réponse immunitaire, comme la production d'anticorps, la réponse cellulaire et l'activité phagocytaire .…”
Section: Adapter Les Animaux à Des Environnements Moins Contrôlésunclassified